Comparative study on failure behavior of promising CMAS-resistant plasma-sprayed thermal barrier coatings in burner rig test with/without CMAS deposition. Issue 8 (15th April 2023) - Fang, Huanjie; Wang, Weize; Zhang, Chengcheng; Wang, Yongxin; Yang, Ting; Yang, Zining; Liu, Yangguang; Ye, Dongdong
Abstract: Along with continuous progress in inlet temperature of turbine engine, calcium-magnesium-aluminum-silicate (CMAS) deposition has become one of serious challenges for traditional yttria partially stabilized zirconia thermal barrier coatings at elevated temperature. Although lots of materials with superior CMAS resistance have been proposed, there is few comparative research on performance of corresponding coatings reported especially when subjected to thermal cycling and CMAS simultaneously. To this end, some coatings were prepared in present study, and thereafter failure behavior in condition of thermal cycling and thermal cycling-CMAS was systemically investigated and compared. Experimental results showed a varied lifetime and cracking behavior in thermal cycling test and thermal cycling-CMAS test, indicating that CMAS infiltration affected failure behavior of coatings. Besides, it was numerically found that CMAS penetration would lead to a promotion of thermal stress, which increased the tendency for cracking during thermal cycling. And the phenomenon that channel crack was the precondition of delamination crack was revealed.